Constructing Community and Consumers: Joseph R. Smallwood’s Barrelman Radio Programme - Webb, Jeff (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1997)
AbstractUnder the name “The Barrelman” Joseph R. Smallwood exhibited a unique collection of oral tradition and historical anecdote in radio broadcasts that aired between 1937 and 1943. Smallwood's radio programme fostered Newfoundland nationalism, yet at the same time it undercut that nationalism by encouraging listeners to want a North American consumer lifestyle. As a commercial programme, it advertised the products of the show's sponsor, EM. O'Leary, and contained an underlying discourse that reconstructed listeners as consumers. Smallwood's nationalism was not unproblematic either. In the economic crisis of the Depression, Smallwood's tales of heroism and success were used to promote a self-reliant popular culture with the aim of creating a cultural change among Newfoundlanders that would improve their economic performance. Since the Newfoundland state was no longer democratic, his nationalist vision was decentred from the state and built upon a foundation of those qualities of the people that Smallwood wanted to encourage.